4-tert-butylpyridine induced Ni3+/Ni2+ ratio modulation in NiOx hole transport layer towards efficient and stable inverted perovskite solar cells. (March 2023) - Hu, Taotao; Hou, Hongming; Peng, Jin; Wu, Qiaofeng; He, Jialong; Yu, Hua; Liu, Rui; Hou, Tian; Zhou, Xiangqing; Zhang, Meng; Zhang, Xiaolong; Yang, Xinchun; et al.
Abstract: NiO x plays a vital role in fabricating efficient and stable inverted perovskite solar cells (PSCs). However, the relatively low conductivity and inefficient hole extraction of NiO x hole transport layer (HTL) due to the low Ni 3+ /Ni 2+ ratio limit its use in high-efficiency PSCs. Here, we report a facile strategy to remarkably enhance the electrical conductivity and hole extraction capability of NiO x HTL by simply introducing the small molecule 4- tert -butylpyridine ( t BP) as additive in the NiO x precursor solution. It is revealed that the t BP efficient improves the charge selectivity of the NiO x interface, inducing the preferable p-type carrier concentration on the surface. Consequently, more oxygen is involved in the process of Ni 2+ to Ni 3+ conversion, and the resulting t BP: NiO x HTL exhibits significantly enhanced hole extraction and transport property. In addition, a thin layer of LiF is applied to passivate the surface of NiO x, which enables improved hole migration ability by the dipole effect of LiF and reduced trap state density of the surface. The inverted PSCs (0.16 cm 2 ) fabricated with t BP: NiO x HTL delivers an enhanced efficiency of 20.2% relative to the control devices (17.5%). t BP: NiO x devices with a large area of 1 cm 2 are also demonstrated, which achieve a decent efficiency of 16% with excellent long-term stability. Graphical abstract: The 4- tert -butylpyridine ( t BP) efficient improves the charge selectivity of the NiO x interface, inducing the preferable p-type carrier concentration on the surface, which results in significantly enhanced conductivity and hole extraction of the NiO x hole transport layer. Moreover, a thin layer of LiF is applied on the surface of NiO x to serve as a passivation layer, leading to improved hole migration ability by the dipole effect of LiF and reduced trap state density on the surface. Consequently, the usage of t BP additive results in a drastically enhanced efficiency of 20.2% for inverted perovskite solar cells while the LiF interlayer provides a favorable protection ability for the stability of perovskite. Image 1 Highlights: 4- tert -butylpyridine additive improves the charge selectivity of NiO x interface. LiF modifier enables elevated hole migration ability of NiO x by the dipole effect. 20.2% and 16.0% efficiencies are gotten for 0.16 cm 2 and 1 cm 2 devices, separately.